TEKNOLOGI SEDERHANA PEMBUATAN PELET DARI LIMBAH KAYU (Simple Technology of Making Pelets from Wood Waste): Wahyu Supriyati 1)*, Alpian1), dan Yanciluk1) - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTEnergy demand increase following to population growth, high exploration costs, rising of the world oil pricesand the difficulty of finding sources of energy fossil. These factors result to the government of many country toimmediately produce alternative energy that is renewable and environmentally friendly.Wood pellets are one source of alternative energy and the availability of raw materials is very easy to found.The raw materials of wood pellet are in the form of waste of exploitation such as the rest of logging, branches andtwigs, industrial timber waste such as scraps, sawdust and bark, agricultural waste. Waste developed into oneproducts will result in higher economic value.Simple technology of making pellets from wood waste is an alternative energy material to meet the energy needsof the community. The opportunity to develop wood pellets as fuel is very wide open because of Indonesia's forestpotential and the large of forest product waste, both from timber industry and.waste.from.exploitationKeywords : simple technology, pellets, wood, waste, energy